Phosphorylated Ataxia Telangiectasia Mutated (pATM) Enzyme-Linked Immunosorbent Assay (ELISA) for Predicting Radiation Induces Normal Tissue Toxicity in Radiotherapy Patients: A Systematic Review - Sofiati Purnami; Viria Agesti Suvifan; Dwi Ramadhani; Yanti Lusiyanti; Darlina Darlina; Nastiti Rahajeng; Mukh Syaifudin; Dwi Ari Pujianto; Retno Widowati (Indonesian Journal of Cancer, 2023)
Background: An adverse normal tissue response, such as normal tissue toxicity (NTT), is present in radiotherapy (RT) patients and can limit the effectiveness of the RT treatment. Identifying patients with adverse tissue responses before RT had clinical benefits and individual radiosensitivity (IRS) is considered an important factor in NTT incidences. Therefore, this systematic study aimed to determine the possibility of using phosphorylated Ataxia Telangiectasia Mutated (pATM) Enzyme-Linked Immunosorbent Assay (ELISA) to predict NTT in RT patients.Methods: A comprehensive data search was conducted in three electronic databases, namely PUBMED CENTRAL, ScienceDirect, and SCOPUS. The quality of relevant publications was independently evaluated using the PICO (participants, intervention/exposure, comparison, and outcome) approach.Results: : A total of 47 articles were retrieved, 41 of which were assessed based on the titles and abstracts. Furthermore, 39 articles were excluded, and 2 were included in this study.Conclusions: The phosphorylated ATM ELISA on lymphocytes showed promising results for IRS prediction in RT patients. However, these assumptions should be validated on a larger RT patient cohort.